Family-mediated migration infrastructure: Chinese international students and parents navigating (im)mobilities during the COVID-19 pandemic. Issue 1 (1st January 2022) - Hu, Yang; Xu, Cora Lingling; Tu, Mengwei
Abstract: The outbreak of the COVID-19 pandemic and associated responses such as border closure, lockdown measures and flight curtailment have severely disrupted transnational infrastructures that sustain, channel, organize and condition international migration. This infrastructural disruption has led to the double exclusion of temporary migrants from both sending and host societies. In this context, we explore how Chinese international students in the United Kingdom and their parents in China navigate transnational (im)mobilities during the pandemic. In doing so, we develop the conceptualization of "family-mediated migration infrastructure" to elucidate the role played by transnational family relationships in brokering information, mobilizing resources, and coordinating disjointed acts of institutional players in order to sustain transnational (im)mobility. We also reveal a distinctive emotional double-bind in the process of family-mediated infrastructuring, which requires members of transnational families to strategically perform emotional engagement and detachment in complex ways. Our findings highlight the functional resilience and emotional vulnerability of family-mediated transnational migration infrastructure, and render visible the intimate fabrics that contribute to sustaining transnationalism during the pandemic.